Qiyām-i Gawhar-i Shād (VIzārāt-i Irshād-i Islāmī, Idārah-i Kull-i Tablīghāt va Intishārāt, 1982)
Criticism of the repressive policies of Reza Shah-Pahlavi, Shah of Iran, 1878-1944, with special reference to a bloody demonstration held against him at Mashhad in 1935.